2021
DOI: 10.5005/jp-journals-10005-1910
|View full text |Cite
|
Sign up to set email alerts
|

Cheiloscopy and Dactyloscopy as Behavior Assessment Tool in Dental Settings: A Cross-sectional Study

Abstract: A bstract Purpose Assessment of children's behavior in the dental setting and its correlation with thumb print and lip print. Materials and methods The behavior pattern, lip print pattern, and thumb print pattern of 518 children aged 5–12 years were recorded in their first dental visit. The behavior pattern, lip print pattern, and thumb print pattern were determined using Frankl's Behavior Rating Scale, Tsuchihashi's classification, and Cummin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[ 12 ] Singh and Majumdar found that people with arches are centered, competent, and friendly, whereas people with whorls on any finger are abrasive and unyielding. [ 13 ] According to White, the arch represents a person with an accepting nature. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Singh and Majumdar found that people with arches are centered, competent, and friendly, whereas people with whorls on any finger are abrasive and unyielding. [ 13 ] According to White, the arch represents a person with an accepting nature. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%